Windows Azure Platform - Redkar, Tejaswi (New York : Apress L. P., 2009)
Annotation The Azure Services Platform, widely known simply as Azure, is Microsofts eagerly anticipated cloud operating system. It has been in development for the last two years and its release date has now been confirmed for November 2009. Usage data for other cloud operating systems, produced by Google and Amazon, shows that demand for this type of service can be very high.Pro Azure provides a complete A-Z guide for transferring developers existing .NET programming skills across to the Azure cloud environment. It combines architectural overviews of the platforms key components with nuts-and-bolts code examples and fully worked application templates that guide developers through the design, development and deployment sequence to create fully working Azure services.After reading this book developers will have all the information they need to build high quality Azure services of their own.